Pemberdayaan Masyarakat Desa Melalui Pembangunan Infrastruktur Sosial dan Edukasi di Desa Samaenre - Asisah, Nur; Asriani, Fenda; Asan, Asan; Pramawati, Neli; Pebriansa, Muh. Aksan Pebriansa; Vani, Nur; Indriani, Rini; Alkiana, Riska Sisilia; Sapril, Sapril; Intan, Nur; Hakiki, Nurul; Saguni, Dewi Sulfa (Lembaga Dongan Dosen, 2024)
Rural development plays an important role in improving community welfare and equitable development in Indonesia. Samaenre Village, which has abundant natural resource potential, still faces a number of challenges in terms of education, infrastructure, and health. This study aims to provide solutions to four main problems: the unavailability of school name gates, unclear hamlet boundaries, lack of education about healthy snacks, and low literacy skills of students at SDN 1 Samaenre Village. The methods used include data collection through observation and interviews, as well as the implementation of a structured community empowerment program. The results of the community service show that the construction of school gates helps strengthen school identity, the affirmation of hamlet boundaries reduces the potential for administrative conflict, education about healthy snacks increases students' awareness of the importance of nutritional intake, and literacy assistance successfully improves students' literacy skills. This program has a positive impact on improving the quality of education, health, and welfare of the Samaenre Village community.